Extension of the Eeigenvalue-Based Selection Index Method for Fixation of Multiple Trait-Transgressive Segregates in Mungbeans (Vigna radiata L. Wilczek) - Jambormias, Edizon; Sutjahjo, Surjono H; Mattjik, Ahmad A; Wahyu, Yudiwanti; Wirnas, Desta; Patty, Jacob R (Universitas Pattimura, 2024)
The selection of the early generation is a viable strategy for the rapid development of new plant varieties. In mungbeans (Vigna radiata L. Wilczek), the selection process is carried out to obtain high seed yield, early maturity, and sufficiently large seed size. To enhance this process, the extension of the combined-eigenanalysis selection index method (CESIM) with transgressive segregation variables can be used to fix multiple-trait transgressive segregates. Therefore, this research aimed to (1) develop an eigenvalue-based selection index method in information from relatives analysis capable of fixing multiple-trait transgressive segregates in the early generation, (2) predict expected and realized multiple-trait selection responses, and (3) verify the presence of multiple-trait transgressive segregates in the early generation of mungbeans. The material used consisted of the F3 generation population and its selection outcomes in F4, originating from the crossbreeding of mungbean varieties Gelatik × Lasafu Lere Butsiw. The empirical breeding values (EBV) between and within families were obtained using the BLUP values of the F3 generation from the mixed linear model with a nested design and log-normal distribution. The EBV values between families and dummy variables of transgressive segregate families were used in the selection process with CESIM. Furthermore, analysis of variance in EBV values within families in the F4 generation was applied to verify the presence of multiple-trait transgressive segregates. The results showed that the selection from the best CESIM equation yielded index scores with a determination coefficient R2 = 97.76% and an expected selection response of 136.62. The verification process confirmed the presence of 9 families as multiple-trait transgressive segregate families in the early generation.